2016
DOI: 10.18632/oncotarget.7719
|View full text |Cite
|
Sign up to set email alerts
|

High blood sugar levels significantly impact the prognosis of colorectal cancer patients through down-regulation of microRNA-16 by targeting Myb and VEGFR2

Abstract: The high prevalence of type 2 diabetes mellitus in colorectal cancer patients is a crucial public health issue worldwide. The deregulation of microRNAs has been shown to be associated with the progression of CRC; however, the effects of high blood sugar levels on miR deregulation and, in turn, CRC remain unexplored. In this study, 520 CRC patients were classified into two groups according to their blood sugar levels (≧110 or <110 mg/dL). Clinicopathologic features, clinical outcomes, and serum miR-16 levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 53 publications
1
46
1
Order By: Relevance
“…In our meta-analysis, year of publication ranged from 2003 to 2016, and the regions included 2 American countries[7, 1315, 18, 19, 27, 30, 33, 37, 41, 42, 45, 46], 6 European countries[6, 11, 17, 28, 32, 39, 40, 44], 2 Asian countries[8, 9, 12, 16, 20, 29, 3436, 38, 43, 47] and 1 Oceania country[31]; the included studies contained 15 retrospective[9, 10, 14, 16–20, 27, 33, 36, 37, 39, 41, 47] and 21 prospective[68, 1113, 15, 2832, 34, 35, 38, 40, 4246] cohort studies; the sample size ranged from 391 to 1056243, and the mean age of study ranged from 46.4 to 72.07. In DM ascertainment, 25 studies[6, 8, 9, 1115, 18, 19, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our meta-analysis, year of publication ranged from 2003 to 2016, and the regions included 2 American countries[7, 1315, 18, 19, 27, 30, 33, 37, 41, 42, 45, 46], 6 European countries[6, 11, 17, 28, 32, 39, 40, 44], 2 Asian countries[8, 9, 12, 16, 20, 29, 3436, 38, 43, 47] and 1 Oceania country[31]; the included studies contained 15 retrospective[9, 10, 14, 16–20, 27, 33, 36, 37, 39, 41, 47] and 21 prospective[68, 1113, 15, 2832, 34, 35, 38, 40, 4246] cohort studies; the sample size ranged from 391 to 1056243, and the mean age of study ranged from 46.4 to 72.07. In DM ascertainment, 25 studies[6, 8, 9, 1115, 18, 19, …”
Section: Resultsmentioning
confidence: 99%
“…In DM ascertainment, 25 studies[6, 8, 9, 1115, 18, 19, 28, 29, 31, 3337, 3942, 4446] used the method of medical records, 5 studies[16, 20, 38, 43, 47] used the method of blood sugar test, and 6 studies[7, 10, 17, 27, 30, 32] used the method of self-reported. To avoid the effects of confounders, we preferred to extract the adjusted outcome effect estimates, but we still found that the outcome effect estimates of 4 studies were not adjusted.…”
Section: Resultsmentioning
confidence: 99%
“…For the wound-healing assay, as described in earlier studies [7478], cells were plated and the monolayer of the cells was gently scratched with sterile micropipette tips, washed twice with PBS to remove cell debris, and incubated at 37°C with serum-free culture medium for serum starvation. The area of the gap at 0 h and the residual gap at 36 h after wounding of five random locations were acquired using a digital camera and microscope.…”
Section: Methodsmentioning
confidence: 99%
“…In a meta-analysis including 26 observational studies in patients with colorectal cancer [13] it is found that diabetic patients have a 17% increased risk of all-cause mortality and a 12% increased risk of cancer-specific mortality, compared to those without diabetes. The disease-free survival and overall survival of the CRC patients were also associated with blood glucose levels in a multivariate analysis [14]. Results from one pathologic analysis has found that patients with diabetes have deeper tumor invasion, greater lymphovascular invasion, and higher TNM staging compared to those without diabetes [15].…”
Section: Epidemiological Association Between Type 2 Diabetes and Cmentioning
confidence: 99%